2019
DOI: 10.1055/s-0038-1677004
|View full text |Cite
|
Sign up to set email alerts
|

Diverting Ostomy: For Whom, When, What, Where, and Why

Abstract: Fecal diversion is an important tool in the surgical armamentarium. There is much controversy regarding which clinical scenarios warrant diversion. Throughout this article, we have analyzed the most recent literature and discussed the most common applications for the use of a diverting stoma. These include construction of diverting ileostomy or colostomy, ostomy for low colorectal/coloanal anastomosis, inflammatory bowel disease, diverticular disease, and obstructing colorectal cancer. We conclude the followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
(26 reference statements)
0
17
0
2
Order By: Relevance
“…reviewed 525 cases of low rectal cancer having rectal resection with CAA, with or without a proximal stoma, and the results revealed that, in cases of CAA without fecal diversion, there was a significantly greater incidence of sepsis ( P = 0.022), septic shock ( P = 0.018) and need for reoperation ( P = 0.0001) than those with diversion, and the length of hospital stay was significantly longer with CAA without diversion [ 4 ]. A diverting loop ileostomy is preferred to loop colostomy, and an ostomy should be used for a pelvic anastomosis <5–6 cm, including CAA and ileoanal pouch anastomosis [ 5 ]. DCAA, the so-called Turnbull and Cutait procedure was originally developed as an alternative to straight CRA in adult patients with mid-rectal cancer or rectal Chagas and children with Hirschsprung disease to avoid permanent stoma [ 6–8 ].…”
Section: Discussionmentioning
confidence: 99%
“…reviewed 525 cases of low rectal cancer having rectal resection with CAA, with or without a proximal stoma, and the results revealed that, in cases of CAA without fecal diversion, there was a significantly greater incidence of sepsis ( P = 0.022), septic shock ( P = 0.018) and need for reoperation ( P = 0.0001) than those with diversion, and the length of hospital stay was significantly longer with CAA without diversion [ 4 ]. A diverting loop ileostomy is preferred to loop colostomy, and an ostomy should be used for a pelvic anastomosis <5–6 cm, including CAA and ileoanal pouch anastomosis [ 5 ]. DCAA, the so-called Turnbull and Cutait procedure was originally developed as an alternative to straight CRA in adult patients with mid-rectal cancer or rectal Chagas and children with Hirschsprung disease to avoid permanent stoma [ 6–8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CD, the indications for permanent ostomy creation are proctectomy or abdominoperineal excision for unresponsive perianal disease [3, 5, 6, 16] while for temporary diverting ostomy are refractory but potentially remissible perianal CD [7] and ileocolectomy and primary anastomosis, often at increased risk of anastomotic leak [8]. In patients with CD, creating an intestinal stoma is commonly the last resource of an often emergent and complicated operation under difficult circumstances.…”
Section: Methodsmentioning
confidence: 99%
“…A temporary ostomy can be performed to increase the quality of life in patients with the severe fistulizing perianal disease and fecal incontinence, to protect a high-risk anastomosis, or in case of postoperative complication, anorectal stricture, colitis, or proctosigmoiditis. Permanent ostomy is necessary after proctectomy or abdominoperineal excision and proctectomy is a common procedure in patients with unresponsive perianal CD [3, 5, 6]. Temporary fecal diversion may improve symptoms in approximately two-thirds of patients with refractory perianal CD while a permanent ostomy and a proctectomy is a common procedure in patients with severe and completely unresponsive perianal CD [7].…”
Section: Introductionmentioning
confidence: 99%
“…These wounds are seen with immobile or poorly perfusing patients that can become infected and progress to cellulitis, abscess formation, and even osteomyelitis [ 4 ]. These wounds require regular dressing changes to keep the site clean but can be a big challenge for caregivers due to the ulcer's proximity to the anus where feces can easily contaminate the sacral ulcer [ 1 , 2 ]. Newer methods have been created to help cut down contamination and improve healing in chronic wounds.…”
Section: Introductionmentioning
confidence: 99%
“…
Introduction Diverting ostomies are traditionally used as a bridge to primary resection in patients with an obstructing mass, or severe inflammatory bowel disease [ 1 ]. In some cases, severe infections or non-healing wounds can be better managed after the diversion of fecal material away from the area [ 2 ].
…”
mentioning
confidence: 99%